Desarrollo de un plan estratégico de marketing para la Empresa Wissgroup SAC. - Cenas Zegarra, Santiago Iván (2019)
This work entitled "Developing a Strategic Marketing Plan for the Company WISSGROUP S.A.C." has as main objective to contribute to the Company in achieving its goals by implementing marketing strategies to achieve higher sales and consolidate a greater market position. The development of this work begins with an analysis of the industry environment in which the Company operates, identifying opportunities and threats. Also performed an internal analysis of SAC WISSGROUP to obtain more precise information of their real market situation, where they identified the strengths and weaknesses of it. With the above information and the use of analytical tools such as SWOT Matrix, Matrix SPAE (Strategic Position and Action Evaluation), Factor Evaluation Matrix Internal - External Grand Strategy Matrix and Matrix Quantitative Strategic Planning (MQSP), was raised and chose the most appropriate strategies for SAC WISSGROUP Subsequently, the Action Plans were established for the years 2012 to 2014 to implement the proposed strategies. Finally, economic evaluation was established, where the project's viability determined by assessing the NPV (Net Present Value) which has the value of S /. 592.40. and IRR (Internal Rate of Return) of 28.7%.